The Effect Of Training Methods Speed Play On 100 Meter Run Skills - Raffly Henjilito; Kamarudin Kamarudin; M. Ramadhan Alfansuri Alfansuri (JIPES - JOURNAL OF INDONESIAN PHYSICAL EDUCATION AND SPORT, 2021)
The purpose of this study was to determine the effect of the training method speed play on 100 meter running skills. The type of this research is experimental research with one group pree test post test design. Sampling was done by total sampling technique, ie the entire population was used as a sample. The instrument used in this study was the 100 meter running test. From the calculation results, it is known that the correlation value of the pre-test and post-test of the 100-meter run is obtained by the calculated r value = 0.89 with the r table value = 0.423 so that the KD value or contribution value is 79.21%, with the t-test result being 8, 82. Conclusion There is an effect of speed play training method on 100 meter running skills.